Molecular evaluation of early-age plasma adiponectin levels in young obese cases with diabetes mellitus type 1 - Ellethy, Abousree T.; Hagag , Mohamed E. (International Journal of Health Sciences, 2024)
Objectives: Adiponectin (ADN) is related to insulin resistance and cardiovascular disorders risks. It is negatively controlled in obese cases among diabetes mellitus type 1 (DMT1) patients. The current study evaluates ADN levels in early-aged children 9–12 years old of obese and non-obese cases (DMT1). Methods: A cross-sectional study among children aged 9–11 years old, was conducted during the year 2023 within two groups. First was a diabetic children DMT1 group excluding diabetic cases with complications. Second was a healthy children’s control group. Two groups were subdivided into two subgroups, obese and non-obese (n = 6 for each subgroup). ADN concentrations were measured in DMT1 cases related to weight and body mass index among treated and non-treated with insulin-therapy compared to in vitro diabetic rats. Adult albino male rats enrolled in a control group, non-treated diabetic, and insulin-treated diabetic rats. Statistical analysis-based measuring means and standard deviation for each group and comparing them with the student t-test. Results: Significantly increased plasma AND levels were detected in DMT1 patients compared to non-diabetic cases (P < 0.001). AND levels were decreased in obese rather than non-obese cases of control or diabetic cases (P < 0.001). Data shows significantly increased plasma AND levels in experimental rats, induced with diabetes (with or without insulin treatment) compared to the control group (P < 0.001). Conclusion: Plasma ADN levels were significantly reduced in obese subjects’ diabetics or non-diabetics. It may refer to insulin resistance or mechanisms that prevent further weight gain by decreasing insulin sensitivity and increasing energy expenditure.